FENOMENA URBAN SPIRITUALITAS SOLUSI ATAS KEGERSANGAN SPIRITUAL MASYARAKAT KOTA - Misbah, Mohammad (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2011)
Modernity has given a great chance to modern people to meet and pursue their material needs in one hand, but on the other hand, they may lose the other essential need like happiness, peace of soul, self identity, and self meaning. They lose the "self" and are alienated from themselves and their own World. The rise of NewAge phenomenon in Indonesia was marked by the birth of various spiritual touch / Sufism (mysticism / Sufism) in orderto meet the needs of the essence, happiness, peace of soul, self identity, and the other meanings that is a manifestation of the human dimension. Sufism emerged in a variety of adivities including thosewhich are not related to the organization tariqat, conventional Sufism, which is a form of organization tariqat, and ecledic mysticism, which is a form of religious diversity. From this came a growing spiritual phenomenon in Indonesia, particularly in urban communities (urbanspiritualitas/ urban Sufism) lately.